Energy Sufficiency of Feed Containing Fermented Mulberry Leaves (Morus alba) Determined by measurement of Glucose, Abdominal Fat and Feed Intake - H. Has; V. D. Yunianto; B. Sukamto (Jurnal Ilmu dan Teknologi Peternakan, 2013)
This study was conducted to determine the effect of using rumen liquid fermented mulberry leaves in boiler’s diet on feed consumption, blood glucose, and abdominal fat. This research used 100 of day old CP 707 broiler chicks, as well as concentrate, fermented mulberry leaves and other feed stuffs. The experiment was carried out according to completely randomized design consisted of five treatments, i.e. T0 (control), T1 (10% mulberry leaf), T2 (10% fermented mulberry leaf), T3 (20% mulberry leaf) and T4 (20% fermented mulberry leaf) and four replications for each treatment. Result of the study showed that the increasing use of mulberry leaves, either fermented or unfermented, significantly (P<0.05) increased feed consumption compared to control. Treatment with 20% unfermented murlberry leaf significantly (P<0.05) decreased fat and glucose levels. This study concludes that 20% murlberry used in diet decrease energy density of diet and the use of 10% fermented mulberry leaf produced better results than unfermented.